PERANAN KAYU SEBAGAI MATERIAL PADA DESAIN PRODUK DAN DESAIN INTERIOR - Arijanto Salmoen Wargadinata (Universitas Trisakti, 2007)
AbstractAs you know wood is natural material as acomposite material is usingfor construction building, interior need, household equipment and (Act; that's way we are talking about wood. We were descript ing woods for a tropical wood as tropical hard wood and tropical soft wood. The process production of it's are variaties, many of processes like's tradi timid processes and modern process style has been knew and now we are talking about the type of wood, the characteristic of wood and special properties of wood. I hope the discription above can opened mind of the product designer for looking more deeply to wood material's. Therefore a professional ity thinking and practice skill for material matters especially wood material's are very importance and should be decided for the future .Abstrak.Seperti kita ketahui kayu adalah bahan alami non komposit, yang banyak digunakan untuk berbagai kebutuhan, antara lain: konstruksi bangunan, kebutuhan interior, peralatanrumah tangga clan sebagainya. Tulisan mi membahas mengenai keberadaan kayu tropis, jenis hard wood clan soft wood. Proses produksi / pengolahan kayu sangat bervariasi, yaitu dengan cara tradisional dan cara modern. Disamping itu juga dibahas jenis, karakter kayu clan manfaatnya. Tulisan ini diharapkan dapat rnembuka wawasan bagi para perancang interior dan perancang produk dalam memanfaatkan bahan kayu untuk kepentingan masa depan.